(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Meharamae Motorcycle parts shop was owned by the Geraldo Family. It was built a year ago. (2009) and MEHARAMAE comes from 4-person names: ME is Melda, Ha is Hazel, Ra is Randy, and Mae is Razel Mae. Meharamae continued their shop, which from small has now grown and has three shops. The findings show that the majority of the respondents are male, ages 21-35; most are single and employed. Then, the study reveals an assessment of two groups of respondents on the product recycling process of Meharamae motorcycle parts in terms of generated ideas. Concept development and commercialization are "Strongly Agreed" The problems encountered by the owner and employees of Meharamae Motorcycle Parts pertaining to the product recycling process are “Affordability of the stocks, price range, customer feedback, and the need for skilled technicians.” Based on the study, the researcher came up with the following discussions: 1. MEHARAMAE should give attention to marketing the business in ages 21-25 and 31-35 because they already established their market in ages 21-35 years, in order to expand the scope of the business. 2. Meharamae Motorcycle parts need to be competitive in terms of generated ideas, concept development, and commercialization. The recycling process needs to be disseminated understandably upon the ordering point. 3. Problems encountered include affordability of the stocks, quality of the stocks, customer satisfaction, and the need for skilled technicians. 4. The store crew needs to be open and politely answer questions or objections referred by the customers about the Old Stocks and other matters. Provide a piece of information regarding the dissemination of the Old Stocks with the purpose of raising the customer’s awareness and avoiding certain objections.